Analysis of Barriers that Affect the Success of the “Zero Waste North Lombok” Program - Suci, Dewinda Prameta; Rakhmatulloh, Anita Ratnasari (ASTONJADRO, 2024)
Waste management is a cross-cutting issue that is closely related to various global challenges. At the local government level, waste management services carried out demonstrate the sustainability of a city so that local governments are responsible for finding affordable waste management solutions with the least impact on the environment. North Lombok Regency has a waste management problem that results in the realization of its handling not reaching the target. To overcome the waste management problem, the local government initiated a priority development program "Zero Waste North Lombok" which is expected to address the existing problems. In the process, the implementation of the program has not run significantly. To support the achievement of the program, a study of the barriers to zero waste was conducted using the fuzzy DEMATEL method. This method is able to facilitate the identification of causal relationships between criteria assessed in complex systems so as to provide information on various perceptions for stakeholders. The 12 barriers identified were divided into two groups: influential barriers and receptive barriers. The influential barriers consist of lack of policies and regulations on waste, lack of cooperation among stakeholders, uncertainty about circular economy targets and strategies, and inadequate sanctions and fines. While the influential group of barriers consists of the barriers of lack of environmental awareness, inadequate recycling techniques, inadequate methods for sorting, transporting and recycling waste, lack of financial and economic assistance, lack of advertising and media coverage for waste management, lack of adequate areas for waste collection and sorting, lack of awareness about environmental protection and lack of temporary shelters. This group of influential barriers needs to be considered and addressed by the local government so that the goals of the "Zero Waste North Lombok" program can be achieved.